The Promises and Limitations of Educational Tiers for Special and Inclusive Education - James M. Kauffman (MDPI AG, 2021)
Making public school accommodating of all learners such that the need for special education is obviated, or at least reduced, has long been a desideratum of educators. Various strategies for making general public education more accommodating of students with disabilities have been tried. The most recent efforts to improve the general education of students with disabilities involve various models of tiered education. Educational tiers can be logical and advantageous in some ways, holding promise for improving general education, but they do not address the core problems of special education. Special education is still needed as part of inclusive education.